Albert Jeremiah Beveridge papers - Beveridge, Albert Jeremiah, 1862-1927.; Beveridge, Albert Jeremiah, 1862-1927.; Beveridge, Albert Jeremiah, 1862-1927.; Beveridge, Albert Jeremiah, 1862-1927.
Correspondence, diary notes, addresses, writings, notes, records of interviews with comments by the subject, printed matter, photographs, and other papers relating to Beveridge's career from his early law practice in Indiana through his two terms in the U.S. Senate, his experience as a war correspondent in Europe, and his work as a historian and biographer. Subjects include the rise of Progressivism, Indiana state politics, American imperialism and support for the annexation of the Philippines, naval development prior to World War I, and child labor laws and other reform legislation. Includes drafts of Beveridge's books, What is Back of the War (1915), Life of John Marshall (1916-1919), and Abraham Lincoln, 1809-1858 (1928), as well as source material used by Beveridge in writing his biography of Abraham Lincoln. Interviewees include Henri Bergson; Edward Grey, Viscount Grey of Fallodon; Gabriel Hanotaux; Gilbert Parker; Bernard Shaw; Alfred von Tirpitz; and William II, German Emporer. Correspondents include George Horace Lorimer, George W. Perkins, David Graham Phillips, Gifford Pinchot, Theodore Roosevelt, John C. Shaffer, and Albert Shaw.
U.S. senator from Indiana, lawyer, historian, and biographer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Card indexes to Series 1 (Office Files) available in the Library of Congress Manuscript Reading Room.
Keywords: Bergson, Henri, -- 1859-1941 -- Interviews; Grey of Fallodon, Edward Grey, -- Viscount, -- 1862-1933 -- Interviews; Hanotaux, Gabriel, -- 1853-1944 -- Interviews; Lincoln, Abraham, -- 1809-1865.; Lorimer, George Horace, -- 1868-1937 -- Correspondence; Marshall, John, -- 1755-1835.; Parker, Gilbert, -- 1862-1932 -- Interviews; Perkins, George W. -- 1862-1920 -- Correspondence; Phillips, David Graham, -- 1867-1911 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Shaffer, John C. -- 1853-1943 -- Correspondence; Shaw, Albert, -- 1857-1947 -- Correspondence; Shaw, Bernard, -- 1856-1950 -- Interviews; Tirpitz, Alfred von, -- 1849-1930 -- Interviews; William -- II, -- German Emperor, -- 1859-1941 -- Interviews; United States. -- Congress. -- Senate; United States. -- Navy; Progressive Party (1912); Child labor -- Law and legislation -- United States; Imperialism; Practice of law -- Indiana; Progressivism (United States politics); Social change -- United States; World War, 1914-1918 -- Causes; World War, 1914-1918 -- Journalists; Indiana -- Politics and government; Philippines -- Foreign relations -- United States; United States -- Foreign relations -- 1865-; United States -- Foreign relations -- Philippines; United States -- Politics and government -- 1865-1933.; United States -- Social conditions; United States -- Territorial expansion; Biographers; Historians; Lawyers; Senators, U.S. Congress -- Indiana